HistoHub: Development of virtual museum for Malaysia’s early history, colonial era and independence - Shojeni, Kumeresan; Nur Shamsiah, Abdul Rahman; Nor Saradatul Akmar, Zulkifli; Noor Azida, Sahabudin (Springer Nature Link, 2025)
This study explores the potential of virtual reality (VR) technology to revolutionise history education in Malaysia. Recognising the limitations of traditional classroom approaches, this study investigates the development of HistoHub, a VR museum dedicated to showcasing Malaysia’s early history, colonial era, and independence. Through a comprehensive literature review, the study establishes the growing prominence of VR in educational settings and its capacity to elevate student engagement and learning outcomes. The problem statement highlights the shortcomings of current history education, particularly in the Malaysian context, and proposes HistoHub as a potential solution. The project outlines a methodical approach encompassing research on existing VR applications in historical education, the meticulous creation of the VR museum, and user acceptance testing to assess its effectiveness. This study contributes to the ﬁeld of educational technology by demonstrating the viability of VR integration in history lessons. HistoHub offers a novel approach to fostering a deeper understanding and appreciation of Malaysian history among students. User acceptance testing results indicate a positive user experience with HistoHub, paving the way for further exploration of VR’s potential in enriching historical learning.